The Impact of Ownership Structure Components on Agency Costs “An Empirical study on th traditional banks listed on the Damascus Securities Exchange” - عثمان هنادي; إياد مالك حاتم (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to test the impact of ownership structure components on agency costs, for a sample of 11 traditional private banks listed on the Damascus Securities Exchange during the period from 2017 to 2021. Quantitative secondary data were collected from the published financial statements of the banks listed on the Damascus Securities Exchange, and analyzed according to the method of ordinary least squares (OLS) using the statistical package SPSS V.25. Agency costs were measured using two indicators: assets turnover rate, the ratio of operating expenses to revenues. As for the ownership structure through: ownership concentration, institutional ownership, foreign ownership, ownership of board members, and the size of the bank was entered as a control variable. The research found that there is a direct and significant effect of the concentration of ownership in the agency costs measured by the asset turnover rate and the ratio of operating expenses, and a direct and significant effect of the ownership of board members in the agency costs measured by the asset turnover rate only, and there is no effect of foreign ownership and institutional ownership in the agency costs measured by the asset turnover rate and the operating expenses ratio.